On Andrews’ Partitions with Parts Separated by Parity - Abdulaziz M. Alanazi (MDPI AG, 2021)
In this paper, we present a generalization of one of the theorems in Partitions with parts separated by parity introduced by George E. Andrews, and give its bijective proof. Further variations of related partition functions are studied resulting in a number of interesting identities.